Dietary fiber inulin mitigates peripheral neuropathy in different stages of diabetes via modulating gut microbiota and metabolites in db/db mice - Ke Li; Wenjun Fu; Yuanyuan Liu; Jing Xue; Xiaoli Yang; Leiwen Wang; Jin Xu; Junbai Ma; Rong Su; Xia Yang; Yuning Sun; Hao Wang (PLoS ONE, 2025)
The pathogenesis underlying diabetic peripheral neuropathy (DPN) remains largely elusive. Due to current unsatisfactory therapeutic approaches, new strategies for the control of DPN are needed. The present study was designed to assess whether inulin could serve as a potential neuroprotection against DPN in diverse stages of diabetes. Leptin receptor-mutant db/db mice were used as a model for DPN to dynamically assess the effects of inulin on DPN in diverse diabetic groups. According to blood glucose, the mice were randomly divided into prediabetes group (PDM group), inulin treated prediabetes group (INU/PDM group), diabetes group (DM group) and inulin treated diabetes group (INU/DM group). After 6 weeks of treatment, we found that inulin supplementation attenuated the neuropathic phenotypes in PDM and DM, including mechanical allodynia, thermal hyperalgesia and nerve conduction. Furthermore, inulin administration remarkably suppressed the levels of pro-inflammatory IL-6, TNF-α, and IL-17A in diverse diabetic groups with DPN, but increased an anti-inflammatory IL-10 in INU/PDM group, suggesting that dietary inulin intervention may suppress the DPN inflammation in different diabetic stages. Moreover, inulin supplementation markedly reduced the circulating LPS translocation. Metabolomics analysis revealed that inulin treatment significantly modulated the levels of 8 stage-specific metabolites; notably, it increased anti-inflammatory, anti-diabetic and neuroprotective metabolites taurine and dodecanoic acid in prediabetic mice, while decreasing pro-inflammatory mediators including oleamide and adrenic acid. In diabetic mice, inulin elevated metabolites including methylation (S-Adenosylmethionine), glucose homeostasis (glucose 6-phosphate), N-acetyl-L-phenylalanine and quinate. These metabolites are implicated in pathways such as bile acid metabolism, fatty acid oxidation, and neurotransmitter regulation, suggesting that inulin may exert neuroprotective effects by restoring metabolic homeostasis in a stage-dependent manner. Furthermore, rectification of gut dysbiosis by dietary inulin administration, with a major impact on increasing intestinal beneficial bacteria |( Bacteroides and Cyanobacteria ) and decreasing pro-inflammatory bacteria ( Ruminiclostridium_6 , Mucispirillum, Deferribacteres and Tenericutes ), exerted a close and complex interactions with metabolites, inflammatory factors, and peripheral neuropathic indicators. Collectively, dietary inulin intervention ameliorated DPN via reshaping gut microbial metabolism and suppressing inflammation, which may potentially provide an effective and safe therapeutics for the control of the disease.